ANALISIS PENGENDALIAN PERSEDIAAN OBAT-OBATAN PADA PUSAT KESEHATAN MASYARAKAT (PUSKESMAS) DI KOTA BANDAR LAMPUNG - Rieka Ramadhaniyah (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2016)
Inventory control of medicine was analyzed by two methods, the first one related to theinternal control of data analysis used in this research is descriptive qualitative field research throughobservations and interviews and distributed questionnaires for the supervision and control ofmedicine supply. And The othe one for calculate the minimum inventory levels using EconomicOrder Quantity (EOQ) and Reorder Point (ROP). By calculation using the method it can be seen theamount of medicine money must be provided in order to avoid gaps stock.The results of the study are the internal control medicine supply has been effectivealthough there are still some shortcomings. Based on the EOQ calculation shows that from theexample of calculation with EOQ method with some medicine samples can be concluded that thecalculation of medicine supplies must be calculated carefully so that the vacancy does not occur sothat the medicine remains available medicine supply.